2020
DOI: 10.1128/jvi.02011-19
|View full text |Cite|
|
Sign up to set email alerts
|

Basic Amino Acid Substitution at Residue 367 of the Envelope Protein of Tembusu Virus Plays a Critical Role in Pathogenesis

Abstract: Tembusu virus (TMUV) is a flavivirus responsible for panzootic outbreaks of severe egg-drop and fatal encephalitis of domestic waterfowl in China. Although TMUV can be attenuated by in vitro passaging, experimental evidence supporting the role of specific genetic changes in virulence attenuation is currently lacking. Here, we performed site-directed mutagenesis on five envelope (E) protein amino acid residues in accordance with the attenuated TMUV generated in our recent study. Our results showed that the Thr-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
0
20
0
Order By: Relevance
“…Except for TMUV-MM1775, all the other TMUVs, including TMUV-TP1906, contain 156-Ser which would not disrupt 154-Asn glycosylation and thus may not affect the glycosylation-associated infectivity of TMUVs in avian species. A recent study showed that the Thr to Lys mutation at residue 367 of the E protein plays a predominant role in viral cell-adaptation and virulence attenuation in ducks [25]. TMUV-TP1906 contains 367-Thr of the E protein and thus may retain the virulence in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Except for TMUV-MM1775, all the other TMUVs, including TMUV-TP1906, contain 156-Ser which would not disrupt 154-Asn glycosylation and thus may not affect the glycosylation-associated infectivity of TMUVs in avian species. A recent study showed that the Thr to Lys mutation at residue 367 of the E protein plays a predominant role in viral cell-adaptation and virulence attenuation in ducks [25]. TMUV-TP1906 contains 367-Thr of the E protein and thus may retain the virulence in the host.…”
Section: Discussionmentioning
confidence: 99%
“…Naïve female mice became infected with TBEV after mating with infected males, with viral RNA detected in embryonal tissues of two of 11 litters [134]. Tembusu virus, a mosquito-transmitted pathogen of poultry, replicates in the ovaries and testes of infected birds [135][136][137][138].…”
Section: Other Flavivirusesmentioning
confidence: 99%
“…Yan et al reported that a single mutation at amino acid residue 156 (S-P) reduced the ability of viral replication and transmission in ducks, and further analysis confirmed that the potential mechanism was composed by the disruption of N-linked glycosylation at position 154 and changes in the conformation of the “150 loop” of the E protein [ 51 ]. Recently, it has been found that the threonine-to-lysine mutation of residue 367 in E protein can attenuate DTMUV [ 52 ]. As research continues, the effects of other proteins on viral replication will be discovered.…”
Section: Overview Of Dtmuvmentioning
confidence: 99%